Potential of Plant’s Bowman-Birk Protease Inhibitor in Combating Abiotic Stresses: A Mini Review (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2015)
Bowman-Birk Inhibitor (BBI) is one of the subfamilies of serine protease inhibitors. Numerousstudies have shown that in plants, BBI functions as part of their defense mechanism againstpathogens and microorganisms. The BBI is also known to have anti-carcinogenic properties.Furthermore, the BBI has been reported to function in controlling abiotic stresses such assalinity and drought stresses.. Abiotic stresses are the major problems in agricultural industry.Therefore, numerous researches have been carried out to characterize the BBI and to determineits roles during biotic and abiotic stresses. This paper presents a review regarding therelationship between Bowman-Birk inhibitor and the plant defensive mechanism against abioticstresses.
Keywords: Bowman-Birk Inhibitor, abiotic, WRIS5, Oxidative stress